Teologi Islam: Argumen Alexander Treiger tentang 'Ilmu Kalam - Fendi Utomo (Aqlania, 2023)
This article examines the ideas of Alexander Treiger in conceptualizing the origins of Kalam in the debate culture of Late Antiquity. This article is important to provide a common thread regarding the origins of kalam based on authentic documents. Treieger's ideas refer to Michael Cook and Jack Tannous who argue that the KalÄm style of argument originates from Christological debates which are then absorbed into Muslim practice through the mediation of Arab Christian circles in Syria and Iraq. Treiger reviews the Science of Kalam on ontological historical aspects and terminological debates, which are rarely highlighted by Muslim scholars. From the results of the analysis of what was studied by Treiger, it was concluded that Treiger argued that the originality of Kalam was divided into three parts namely; the origins of the kalam argument, the debate about Qadar (human free will versus God's destiny) and in the final section discusses three Muslim texts on Qadar which are associated with Hasan bin Muhammad al-Hanafiyah, Umar bin Abdul Aziz and Hasan Al-Bashri. Alexander Treiger is of the view that the science of kalam in general is the influence of Muslim-Christian interactions in Syria. However, unfortunately Treiger does not have enough argumentative data to support his assumption that theology has been influenced by Christianity.